Mental Health and Social Development of Prisoners as a Policy Implication of Correctional Institutions - Nur Rochaeti; Irma Cahyaningtyas (Institute of Medico-legal Publications Pvt Ltd, 2021)
The problem in this research is to analyze the health and social development prisoners in Indonesian prisonsin the future. The research method used is juridical empirical, namely analyzing the formulation of policieson current correctional facilities and the health and social development of prisoners in Indonesian prisonsin the future. The results show that the current formulation policies in coaching prisoners are based onLaw No. 12 of 1995 concerning correction institutions. This policy has not fully provided the rights ofprisoners as assisted citizens. The number of prisoners currently in 33 Regional Offices of Law and HumanRights, only 6 Regional Offices is not overcrowded. This will affect the development of prisoners in prisons.Coaching carried out in prisons at this time has obstacles due to statutory factors, human resources in qualityand quantity as well as the legal culture of the community which has not provided optimal support for thedevelopment of prisoners both inside and outside of prisons. In the future, based on policy studies, it isnecessary to carry out reformulation and reconstruction related to the development of prisoners in prisons